Proposing an agile strategy for a steel industry supply chain through the integration of balance scorecard and Interpretive Structural Modeling - Tizroo, Ali; Esmaeili, Ahmad; Khaksar, Ehsan; Šaparauskas, Jonas; Mozaffari, Mohammad Mahdi (Journal of Business Economics and Management, 2017)
The internal and external environment of all organizations challenges them adapt to the best practices and reconsider their relationship throughout the supply chain. In this paper, the authors have tried to propose an agile strategy for the supply chain of a steel company, which ranks 3rd in Iran in Gross Sale with 16,000 employees, in order to respond quickly to ever-changing needs. To do this, through the literature review the framework of balanced scorecard was utilized to structure agility factors in the supply chain of the steel industry. Then the experts were interviewed to reconcile on the factors identified. Utilizing 24 questionnaires by the use of Interpretive Structural Modeling framework, the relationship and sequence of factors were obtained from experts. The final model developed in the paper presents the agility factors for the steel industry supply chain. Also, these factors are grouped within the four perspectives of the BSC to better enhance the results and pursue action. The ISM method identifies the priority of each factor which provides a better understanding of the underlying relationship of the factors for the managers to implement the strategies more reliably. The proposed model for strategy formulation can be utilized in strategy formulation problems over various types of supply chain.